1992
DOI: 10.1159/000261467
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Caries in situ around Fluoride-Releasing Light-Curing Composites: A Quantitative Model Investigation on Four Materials with a Fluoride Content between 0 and 26 vol%

Abstract: In the literature, secondary caries around composite restorations is reported often. Fluoridated composites are therefore interesting materials because they might reduce or inhibit secondary caries. In this article an in situ model investigation is presented in which the effect of F-releasing composites on enamel demineralisation around an artificial gap of 200 μm width was quantified after 1 month. The fluoride content of the composites varied between 0 and 26 vol%. The beneficial effect of the fluoride relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 11 publications
3
33
1
5
Order By: Relevance
“…Dijkman and Arends 37) found that a monthly cumulative fluoride release of 200-300 μg/cm 2 was sufficient to completely inhibit enamel demineralization. In the present study, Fuji IX GP released a cumulative amount of 283.16 μg/cm 2 of fluoride ions after 30 days.…”
Section: Fluoride Release After Recharging With Naf Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dijkman and Arends 37) found that a monthly cumulative fluoride release of 200-300 μg/cm 2 was sufficient to completely inhibit enamel demineralization. In the present study, Fuji IX GP released a cumulative amount of 283.16 μg/cm 2 of fluoride ions after 30 days.…”
Section: Fluoride Release After Recharging With Naf Solutionmentioning
confidence: 99%
“…In the present study, Fuji IX GP released a cumulative amount of 283.16 μg/cm 2 of fluoride ions after 30 days. Further, Dijkman and Arends 37) suggested that the optimal fluoride concentration range to prevent caries formation at the interface between restoration and tooth tissues should be 5-80 ppm.…”
Section: Fluoride Release After Recharging With Naf Solutionmentioning
confidence: 99%
“…However, in this study and many others, examining the release of fluoride ions from pit-and-fissure sealants and fluoride-containing materials has been done in batch systems with distilled water in vitro, resulting in limitations in evaluating the dynamics of fluoride ions emanating from these materials. Therefore, it is necessary to examine the dynamics of fluoride ions under conditions that are the same as the oral environment, for example, through studying pH cycling and the in situ oral system 5) . Ripa 14) suggested that there were limitations with intentionally adding fluoride to dental materials and devices to prevent dental caries from forming or enamel from demineralizing.…”
Section: Discussionmentioning
confidence: 99%
“…However, secondary caries is still the reason most commonly cited for the replacement of composite restorations 3,9,14 . The deficient marginal adaptation and lack of cavity sealing may allow fluid and bacteria infiltration, leading to caries lesions development in the tooth structure along the restorative interface 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, approaches that inhibit the ingress of metabolic products of biofilm into the microgap between tooth and restoration, increase resistance to demineralization, and/or facilitate remineralization are of considerable clinical interest 6 . As numerous investigations have shown the ability of fluoride-containing materials to inhibit caries activity around restorations, continuing research into the development of other materials for delivering fluoride in a form that will be effective is ongoing 3,6,9,14,16,18,11,19 . Glass-ionomer and resinmodified glass ionomer cements have been formulated as cavity liners 10,15 .…”
Section: Introductionmentioning
confidence: 99%